2023
DOI: 10.3390/mps6040065
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of SARS-CoV-2 (COVID-19) Clinical Mouthwash Protocol and Prevalence of the Oral Pathogen Scardovia wiggsiae: A Pilot Study of Antibacterial Effects

Melika Shayegh,
Chase Sorenson,
Jackson Downey
et al.

Abstract: One protocol in healthcare facilities and dental offices due to the COVID-19 pandemic for reducing the amount of detectable oral SARS-CoV-2 has been gargling with mouthwash for 60 s. This protocol lasts longer than the daily routine for most patients and may have unexpected benefits in reducing oral microbes as a result. This project evaluated the prevalence of the newly identified oral pathogen Scardovia wiggsiae before and after this procedure to determine any measurable effects. Using an approved protocol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Saliva samples were stored in a −80 • C freezer in a biomedical laboratory. Previous research studies isolated DNA from samples using the phenol:chloroform extraction method, as previously described [15,29]. For the current study, DNA samples were identified from the biorepository and assessed using the NanoDrop 2000 spectrophotometer from Fisher Scientific (Fair Lawn, NJ, USA).…”
Section: Dna Analysismentioning
confidence: 99%
“…Saliva samples were stored in a −80 • C freezer in a biomedical laboratory. Previous research studies isolated DNA from samples using the phenol:chloroform extraction method, as previously described [15,29]. For the current study, DNA samples were identified from the biorepository and assessed using the NanoDrop 2000 spectrophotometer from Fisher Scientific (Fair Lawn, NJ, USA).…”
Section: Dna Analysismentioning
confidence: 99%
“…First, this is a retrospective study of previously collected data and may have bias intrinsic to the study sample due to the nature of this low-income, predominantly minority clinic population, which may face significant challenges and barriers to health care access and oral health prevention [ 22 , 39 ]. In addition, the reduced nature of some of the procedures performed during the COVID-19 pandemic may have been due to changes in protocols for dental care, which reduced the number of available openings for treatment, as well as changes in patient or parent behaviors, including delays in care due to safety concerns [ 40 , 41 ]. Finally, additional variables that were not the focus of this retrospective investigation of the associations between pulpotomy, pulpectomy and RCT, such as alternative procedures that include pulp capping or vital pulp therapy, may be indirect confounding variables and can be the subject of future investigations.…”
Section: Discussionmentioning
confidence: 99%